2016
DOI: 10.1038/srep38394
|View full text |Cite
|
Sign up to set email alerts
|

Metal Induced Growth of Transition Metal Dichalcogenides at Controlled Locations

Abstract: Metal induced nucleation is adopted to achieve the growth of transition metal dichalcogenides at controlled locations. Ordered arrays of MoS2 and WS2 have successfully been fabricated on SiO2 substrates by using the patterned Pt/Ti dots as the nucleation sites. Uniform MoS2 monolayers with the adjustable size up to 50 μm are grown surrounding these metal patterns and the mobility of such layer is about 0.86 cm2/V·s. The crystalline flakes of WS2 are also fabricated extending from the metal patterns and the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Inevitably, the as-grown MX2 requires a material transfer from that template to the target substrate. In the bottom-up approach, MX2 single crystals grow by selective lateral growth at well-controlled locations on the large area substrate [8][9][10][11][12][13][14][15] . Understanding the reaction kinetics during the deposition process can enable the development of a selective lateral growth process of MX2 from a pre-existing seed.…”
Section: Introductionmentioning
confidence: 99%
“…Inevitably, the as-grown MX2 requires a material transfer from that template to the target substrate. In the bottom-up approach, MX2 single crystals grow by selective lateral growth at well-controlled locations on the large area substrate [8][9][10][11][12][13][14][15] . Understanding the reaction kinetics during the deposition process can enable the development of a selective lateral growth process of MX2 from a pre-existing seed.…”
Section: Introductionmentioning
confidence: 99%
“…A similar effect has been already reported in case of MoS 2 synthesis assisted by metal seeds. 28,29 It is worth noting that the adlayer islands with a lateral size of over 100 nm are mainly hexagonal (trunked triangles) shaped with a zero degree twisting with respect with the underlying flake, while islands, with 100 nm or lower size, are triangular with a 60° twisting. A statistical evaluation obtained by tens of SEM images reveals that the 95% of the hexagonal shaped islands (average lateral size 347 nm) are 0° rotated while the 97% of the triangular islands (average lateral size 84 nm) are 60° rotated with respect with the underlying MoS 2 monolayer.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23] The CVD approach, which yields high-quality and predominantly monolayer (ML) MoS 2 , is a promising technique for realizing large-scale industrial production, but still faces challenges due to poor control over the precise position and yield of the synthesized monolayer product. In order to obtain localized synthesis of monolayer MoS 2 , different approaches have been employed: the localized deposition of the molybdenum precursors [24][25][26] , the masking with mica substrates 27 or the use of metal seeds [28][29][30] . In particular, gold seeds have demonstrated to be particularly efficient for the deterministic synthesis of monolayer TMDs 28,30 , allowing also the growth of vertically aligned MoS 2 flakes, suitable for hydrogen evolution reaction 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is relatively feasible to synthesize vertically grown SnS 2 nanosheet structures with large surface area via metal‐assisted growth methods. Wang et al reported metal‐induced nucleation of transition metal dichalcogenides at controlled locations; specifically, they successfully demonstrated selectively ordered arrays of MoS 2 and WS 2 flakes by using patterned Pt/Ti dots as nucleation sites. Su et al also reported SnS 2 arrays grown on patterned substrates using various metal pads as nucleation sites.…”
Section: Comparison Of No2 Gas Sensing Performance For Diverse 2d Matmentioning
confidence: 99%